PERFORMANCE ANALYSIS OF GREEN SUPPLY CHAIN MANAGEMENT OF DIAPER RAW MATERIALS - Henry, Henry; Nusraningrum, Dewi (Dinasti International Journal of Digital Business Management, 2020)
X is a company engaged in manufacturing and it is necessary to do a performance measurement in improving supply chain management to be an environmentally friendly Green Supply Chain management. The purpose of this study is to determine the current condition of the company's SCM and then analyze the value of the performance of green supply chain management and propose improvements to the company after knowing the most influential indicators in order to improve the performance of green supply management in the company. Based on the problems studied, the method used in the study is to measure the performance of the company's supply chain using the Supply Chain Operation References (SCOR) method. The initial hierarchy model of performance measurement is adjusted to the condition of the company to measure the performance of its supply chain, while the normalization of Snorm De Boer serves to equalize the matrix value used as an indicator of measurement. The importance of performance attributes is measured based on weighting with subjective questionnaires using AHP. SCM Conditions of PT. X it is known that there are two stages of SCM that have low KPI values, namely manufacturing and distribution. Green supply chain performance measurement results obtained that the calculated performance value is 67.95. This value indicates that the achievement of the performance of the green supply chain management is classified as average and needs to be improved, especially for indicators that have low values